2017
DOI: 10.1007/s00253-017-8346-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sucrose-induced small RNAs in Streptococcus mutans in the presence of different sucrose concentrations

Abstract: Streptococcus mutans (S. mutans) is the major pathogen contributing to dental caries. Sucrose is an important carbohydrate source for S. mutans and is crucial for dental caries. Small RNAs (sRNAs) are key post-transcriptional regulators of stress adaptation and virulence in bacteria. Here, for the first time, we created three replicate RNA libraries exposed to either 1 or 5% sucrose. The expression levels of sRNAs and target genes (gtfB, gtfC, and spaP) related to virulence were assessed. In addition, some phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Initially, a range of concentrations were evaluated (0.125, 0.25, 0.5, 1, 2, and 5% w/v) in terms of biomass and pH, with the resultant biofilm data demonstrating that the carbohydrate source, irrespective of concentration, showed a consistent trend ( Supplementary Figure S2 ), i.e., sucrose consistently gave greater biomass and lower pH, whereas galactose displayed the contrasting polarized effects. We therefore focused on the concentration of 1% w/v with caries-free ( n = 10) and caries ( n = 10) isolates, a concentration which has been a consistently reported within analogous studies ( Zeng et al, 2013 ; Liu S.S. et al, 2017 ; Cai et al, 2018 ). These data showed that although sucrose displayed the greatest biomass and lowest pH, followed by mannose, glucose, fructose and galactose, there were no significant differences between these caries groups in terms of biomass and pH ( Figures 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a range of concentrations were evaluated (0.125, 0.25, 0.5, 1, 2, and 5% w/v) in terms of biomass and pH, with the resultant biofilm data demonstrating that the carbohydrate source, irrespective of concentration, showed a consistent trend ( Supplementary Figure S2 ), i.e., sucrose consistently gave greater biomass and lower pH, whereas galactose displayed the contrasting polarized effects. We therefore focused on the concentration of 1% w/v with caries-free ( n = 10) and caries ( n = 10) isolates, a concentration which has been a consistently reported within analogous studies ( Zeng et al, 2013 ; Liu S.S. et al, 2017 ; Cai et al, 2018 ). These data showed that although sucrose displayed the greatest biomass and lowest pH, followed by mannose, glucose, fructose and galactose, there were no significant differences between these caries groups in terms of biomass and pH ( Figures 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences were observed, and were not only dependent on the sugars, but also on specific isolates. Liu S.S. et al (2017) revealed S. mutans isolates varied in their ability to compete and become dominant in the biofilm after the addition of sucrose ( Liu Y. et al, 2017 ). Interactions between microorganisms colonizing the oral cavity are consecutive factors affecting the development of biofilm, with interactions occurring between microorganisms resulting in both the acceleration and inhibition of this process ( Wen et al, 2010 ; Redanz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, sRNAs coordinate adaptation processes in response to environmental changes in bacteria by regulating target mRNA expression [37][38][39][40][41]. Specifically, srn225147 and srn821798 were sequenced in our previous studies [22,23]. Virulence-related genes selected in our present study were predicted targets for these two sRNAs according to IntaRNA and RNAPredator.…”
Section: Discussionmentioning
confidence: 92%
“…The PCR reaction conditions for srn821798 were as follows: denaturation at 95°C for 10 s; 40 cycles consisting of 5 s of denaturation at 95°C; and 20 s of annealing at 50°C. The primers for 16S rRNA, gtfB, gtfC, spaP, srtA, ffh, and relA were synthesizedaccording to previous studies[8,[22][23][24].…”
mentioning
confidence: 99%
“…surface of a tooth, forming a biofilm and releasing acidic compounds following carbohydrate metabolism, thereby corroding the tooth surface (5). There is strong epidemiological evidence that S. mutans is more commonly detected in the oral cavity of children affected by dental caries compared to that in children free of such caries (6,7), and the forms of S. mutans isolated from children with caries have been found to be more virulent than those isolated from caries-free children (8).…”
mentioning
confidence: 99%